Active geodetic network: application in topography - Enrique Cano-Jódar; Manuel Sánchez-de-la-Orden; Javier Mesas-Carrascosa (Dyna, 2018)
The objective of this work is to determine the positional quality of the solutions offered by the Andalusia Positioning Network (RAP), an active geodetic network located in the autonomous community of Andalusia in southern Spain. Different tests are performed on the services offered by this active network, especially those that use real-time-Kinematic positioning techniques (RTK). Different parameters are analysed, including precision, accuracy and time of resolution of ambiguities. The system is then analysed from the perspective of the topographic survey; several small-scale topographic surveys are carried out, used for mining and civil engineering projects, with the aim of seeing if an active geodetic network can be used with performance similar to that for conventional RTK.